A three-dimensional finite element analysis of Aramany class I obturator fabricated with different alloys - Kashinath C Arabbi; Takshil D Shah; Mahantesha Sharanappa; Shobha K Subbaiah (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of the research was to develop a model that accurately represents an Aramany class I defect and its obturator prostheses fabricated with cobalt-chromium alloy and titanium alloy to compare the deflection and the stress distribution in the rehabilitated area. Materials and Methods: Aramany class I defect and the obturator prostheses were generated geometrically using ANSYS 14.5; both were superimposed on each other to mimic the prostheses and the maxilla as one unit. Meshing of models was carried out using hypermesh software and materialistic properties were assigned. The 120 newton load was constituted on the teeth in different directions. Statistical Analysis Used: Statistical analysis of Finite element was not possible. Self-explanatory decoding results in the software were used. Results: The stress distribution and deflection executed by ANSYS provided results that enabled the tracing of Von Mises stress and deflection field in the form of color-coded bands with values in mega pascal. Conclusions: The study shows that Von Mises stresses are higher for the frame work fabricated with cobalt-chromium alloy compared to titanium alloy. The framework made of titanium alloy showed more deflection than cobalt-chromium alloy.